Parque lineal Pedro Pizarro. Propuesta de diseño urbano para la revitalización del espacio público en el centro de la ciudad de Florencia, Caquetá (2021)
Florencia, Caquetá is an intermediate city that has grown in a disproportionate and disorderly manner from the informal settlements of people who are victims of the armed conflict and the geographical characteristics of the region, which has unleashed a series of problems related to the deficit of public space and problems of accessibility, which reflects little urban cohesion and urban vitality; it is worth noting that there is a deficit of cultural and sports facilities. In response to these problems, urban design strategies are proposed, using land management tools, to recover the road layout of Carrera 11, which is the articulating axis of the city, where most of the cultural facilities and nodes are located.